Code Switching Used by Indonesian K-Pop Fans on Twitter - Rifdayanti; Samsudin Hi Adam; Indry Widyasti Anwar (FKIP Universitas Khairun, 2026)
This research aims to identify the types and functions of code switching used by Indonesian K-pop fans on Twitter. A qualitative descriptive method with a content analysis approach was employed in this study. A total of 40 tweets were collected through documentation from active Indonesian K-pop fan accounts that exhibit code switching. The analysis is based on Poplack’s (1980) classification of code switching types and Hoffman's (1991) framework for its functions. The findings show that Indonesian K-pop fans use three types of code switching: intra-sentential switching (19 cases), inter-sentential switching (18 cases), and tag switching (3 cases), with intra-sentential switching being the most dominant. Regarding the functions, the results reveal that code switching is used for talking about a particular topic (8 cases), being empathetic about something (expressing solidarity) (13 cases), quoting somebody else (1 case), intention of clarifying the speech content for the interlocutor (3 cases), interjection (inserting sentence fillers of connectors (3 cases), and expressing group identity (12 cases). The most dominant function is being empathetic about something (expressing solidarity).